THE UTILIZATION OF DIGITAL LITERACY IN CHARACTER-BASED ENGLISH LANGUAGE LEARNING - Syarifuddin, Salmia; Madjid, Abd; Hasyim, Irmawaty (FKIP Universitas Khairun, 2025)
The purpose of this research is to understand how digital literacy is utilized in English language learning within the Faculty of Letters, Universitas Muslim Indonesia (UMI). In addition, this research also aims to provide solutions to the problems and obstacles faced by English lecturers when operating the features on the Learning Management System (LMS) Kalam UMI while still adhering to character education. This research uses a quantitative method with a survey approach. The population in this study consists of lecturers in the English Literature and English Education programs at the Faculty of Letters, UMI. The research sample uses total sampling. The research sample includes lecturers from these programs who teach English both within the Faculty of Letters and across faculties at UMI, who have been using the LMS Kalam UMI for several semesters in the teaching process. The findings of this research indicate that the difficulties faced by lecturers in implementing learning through the LMS Kalam UMI lie in the use of web/live conference features and student reports in the LMS Kalam UMI. The research results show that the utilization of digital literacy in English language learning within the Faculty of Letters, Universitas Muslim Indonesia, has been implemented massively and comprehensively in the learning process.